2004
DOI: 10.1074/jbc.m311655200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced, p38-dependent Apoptosis in Cells Expressing High Levels of Epidermal Growth Factor Receptor and ErbB-2

Abstract: Increased expression of the epidermal growth factor (EGF) receptor (EGFR) and ErbB-2 is implicated into the development and progression of breast cancer. Constant ligand-induced activation of EGFR and ErbB-2 receptortyrosine kinases is thought to be involved in the transformation of fibroblasts and mammary epithelial cells. Data herein show that ligand stimulation of cells that express both the EGFR and the ErbB-2 may result either in cell proliferation or apoptosis depending on the expression levels of EGFR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 54 publications
4
45
0
Order By: Relevance
“…However, the role of the subcellular localization of PKCy in this effect was not reported. We found that the PKCy-Cyto induced the phosphorylation of MKK3/MKK6, which lies upstream of p38 (48). Although PKCy-Cyto activated the p38 pathway, it played only a partial role in the apoptosis induced by the PKCy-Cyto because the p38 inhibitor SB203580 and silencing of p38 only moderately inhibited cell apoptosis, suggesting that additional signaling pathways mediate the apoptotic effect of the PKCyCyto.…”
Section: Discussionmentioning
confidence: 80%
“…However, the role of the subcellular localization of PKCy in this effect was not reported. We found that the PKCy-Cyto induced the phosphorylation of MKK3/MKK6, which lies upstream of p38 (48). Although PKCy-Cyto activated the p38 pathway, it played only a partial role in the apoptosis induced by the PKCy-Cyto because the p38 inhibitor SB203580 and silencing of p38 only moderately inhibited cell apoptosis, suggesting that additional signaling pathways mediate the apoptotic effect of the PKCyCyto.…”
Section: Discussionmentioning
confidence: 80%
“…For example, activation of p38 and/or JNK stress MAPK pathways has been shown to be required for a cell-death response after treatment with cancer therapeutic agents such as adriamycin (98), etoposide (99), cisplatin (100), UV radiation (7,101), gamma-irradiation (102) and even ligand epidermal growth factor (EGF) (103) in various systems. p38 activation, however, was also found to be anti-apoptotic in melanoma (104) and glioma cells (105) in response to UV radiation.…”
Section: The Roles Of the P38 Pathway In Regulating Cell Deathmentioning
confidence: 99%
“…It is worth noting that EGF-mediated apoptosis is not is something that is commonly associated with EGFR signaling in the context of developmental biology, maintenance of healthy tissue, or cancer biology. However, among cell lines that overexpress the EGFR, such as MDA-MB-468 cells and A431 cells, EGF-mediated apoptosis has been well described (Armstrong et al, 1994;Gill and Lazar, 1981;Kottke et al, 1999;Tikhomirov and Carpenter, 2004). Further, indirect evidence for the role of apoptosis in cancer biology has been suggested by Tikhomirov and Carpenter.…”
Section: A Biochemical Analysis Of Egfr Signaling Using Egf-beadsmentioning
confidence: 96%
“…They note that in the literature, more moderate levels of ErbB receptor tyrosine kinases are associated with more invasive carcinomas. They suggest that the induction of apoptosis in cell lines with higher levels of ErbB receptor expression generates a cancer cell whose growth and metastasis is self limiting (Tikhomirov and Carpenter, 2004). Of course, the easiest explanation for the differences in cell survival following EGF and EGF-bead treatment would be that the EGF-beads were not adequately stimulating the receptor.…”
Section: A Biochemical Analysis Of Egfr Signaling Using Egf-beadsmentioning
confidence: 99%